History of proximal femur fractures in the German literature - Bartoníček, Jan; Rammelt, Stefan; Naňka, Ondřej (International orthopaedics, 2024)
INTRODUCTION: German-speaking surgeons have left a deep imprint on the history of diagnostics and treatment of proximal femur fractures. Some of the studies published in German have fell into oblivion, others are cited until today, although sometimes quite inaccurately. The cause of such inaccuracies are citations from secondary sources due to unavailability of the original or inability to read it because of a language barrier. In the current literature, globally predominated by English articles, the "German history" of treatment of proximal femur fractures remains undervalued. The aim of the present article is to point out its contribution. MATERIALS AND METHODS: Literature search was performed in original publications and historical sources. RESULTS: The German-speaking surgeons have considerably contributed to the development of the treatment of proximal femur fractures. The analyzed period between 1847 and 1970 may be divided into three basic periods. In the first period (1847-1896), the German-speaking surgeons (Langenbeck, Trendelenburg, König, Heine, Dolinger) were the first worldwide to start treating the fractures of proximal femur operatively. In the second period (1897-1935), mainly in the 1930s, the initiative in Europe was taken over by surgeons publishing studies in France and in Belgium. Overseas, American surgeons were coming to the forefront. In Germany, only Pauwels developed the first biomechanical classification of femoral neck fractures. In the third period (1936-1970), mainly in the 1940s and 1950s, implants were designed (Pohl, Künstcher), based on close collaboration between German engineers and surgeons, that served as a model for a dynamic hip screw and a proximal femoral nail, which are currently the implants of choice in the treatment of trochanteric fractures. CONCLUSION: The historical contribution of German-speaking surgeons to understanding the issue of proximal femur fractures and their operative treatment is far more significant than presented in the historical studies published in English.
Keywords: fraktury krčku femuru; Femur; fraktury kyčle; Femoral Neck Fractures; Hip Fractures; fraktury proximálního femuru; femur; Fracture Fixation, Internal; Humans; German literature; History; Internal fixation; Bone Nails; Proximal femur fractures; vnitřní fixace fraktury; Proximal Femoral Fractures; lidé; kostní hřeby